Early Detection of Early Childhood Growth and Development - Amaludin, Roni; Idhayani, Nurul; Usman; Hermanto; Permatasari, Sri Jumiaty; Ribani, Wiwin Dewi Fitriani; Ribani, Iin Sri Apriani (Jurusan PG-PAUD Universitas Halu Oleo,, 2024)
The purpose of this study was to analyze the detection of early childhood growth and development at Wulele Sangula Kindergarten. Preventing developmental disorders in early childhood is essential because early childhood is a vulnerable period to negative influences. This type of research is a field survey that collects and analyzes the growth results of early childhood. Data collection techniques were conducted using anthropometric measurements of early childhood, interviews, and documentation studies. The sample of this study was 61 students enrolled in Wulele Sangula Kindergarten. The study found that most early childhood at Wulele Sangula Kindergarten have normal growth and development. However, some early childhood are at risk of malnutrition, some are overweight or obese, and a few show symptoms of microcephaly and macrocephaly. There is a need for psychoeducation for parents of early childhood and early childhood education units regarding Early Detection of Child Growth and ways to address and minimize growth disorders